Dialectics instead of dichotomy: Perspectives on the twin ambition of the disability movement. - Eriksson, Lisbeth (Education Policy Analysis Archives, 2013)
This article discusses the mobilizing work of a disability organization, at the local chapter level. I have spent about a year following the work of a chapter, mainly through contacts, conversations and interviews with the persons who are active on its board. The analysis of the chapter’s work takes as its starting point two traditions that emphasize collective sense of community and mobilization of groups. These traditions, continental social pedagogy and Anglo-Saxon community development, are complemented by the theoretical concepts of recognition and redistribution. A number of dilemmas, which can be expressed in terms of dichotomies, are built into these theories. They can be challenged in different ways by the empirical data. Through these confrontations, we can see how the dichotomy is transformed into dialectics where phenomena cannot be regarded as either or but rather as both.